The effects of lithium chloride in N-methyl-N-nitrosourea induced retinal damage in rats - Incili, Canan Akdeniz; Eroksuz, Yesari; Eroksuz, Hatice; Aslan, Abdullah (Elsevier Ireland Ltd, 2026)
The aim of the current study was to assess the potential neuroprotective effects of lithium chloride (LiCl) against retinal degeneration (RD) induced by N-methyl-N-nitrosourea (MNU) in the rats. 108 rats were assigned to 6 groups: Control, MNU (80 mg/kg), MNU + 30 mg/kg LiCI, MNU + 60 mg/kg LiCI, 30 mg/kg LiCI, and 60 mg/kg LiCI. The experimental groups comprised 18 rats each and the animals were euthanised on the 2nd, 7th and 14th days following the administration of MNU. Compared with the MNU group, both doses of LiCl significantly reduced retinal cell apoptosis and increased retinal thickness (P < 0.05). MNU group had a higher apoptotic index than the treatment groups, as evidenced by increased immunoreactivities of caspase-3, caspase-6, Bax, and 8-OHdG and decreased immunoreactivities of Bcl-2 at day 2. The outer nuclear layer (ONL) of the retina in rats treated with MNU exhibited a significant reduction in comparison the control group on both days 7 and 14 (P < 0.05). In contrast to the MNU-treated figgroup, the LiCl-injected rats exhibited a notable elevation in the expression levels of BDNF and Bcl-2 (P < 0.05). Conversely, the MNU-treated group exhibited markedly increased expression of GSK-3 beta, Bax, 8-OHdG, caspase-3, and caspase 6 (P < 0.05). In conclusion, LiCl demonstrated dose-dependent neuroprotective effects against MNU-induced RD in rats. These effects included a reduction in retinal cell apoptosis, an improvement in retinal thickness, and the potential involvement of anti-apoptotic mechanisms, glial activation inhibition, and neurotrophic factor modulation.
Keywords: Lithium chloride; N-methyl-N-nitrosurea; Rat; Retinal degeneration; Histopathology; Immunohistochemistry